2021
DOI: 10.1007/s13127-021-00504-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards a global list of accepted species V. The devil is in the detail

Abstract: A consensus among biologists has been growing in recent years for the development of a global list of accepted species (and other taxa). To date, much discussion has focused on visions for how such a list would benefit many scientific and societal disciplines. Less emphasis has been placed on understanding the many technical challenges of compiling and maintaining such a list. Challenges include details of implementation such as defining what each entry on the list represents, the scope (taxonomic breadth), gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Given the uncertainty in the validity of some taxa, Kitchener et al (2022) developed a traffic-light system, which indicates the level of certainty in support of the recognition of each taxon that typically included morphological, genetic and biogeographical supporting data. Similarly, Pyle et al (2021) suggested that challenges in the development of global species lists include defining what each taxon represents, the scope or breadth of the taxonomic work, the ranks that are covered (e.g. unnamed taxonomic units, www.publish.csiro.au/am Australian Mammalogy species only, or all ranks), and the level of confidence in the taxon.…”
Section: Species Listsmentioning
confidence: 99%
“…Given the uncertainty in the validity of some taxa, Kitchener et al (2022) developed a traffic-light system, which indicates the level of certainty in support of the recognition of each taxon that typically included morphological, genetic and biogeographical supporting data. Similarly, Pyle et al (2021) suggested that challenges in the development of global species lists include defining what each taxon represents, the scope or breadth of the taxonomic work, the ranks that are covered (e.g. unnamed taxonomic units, www.publish.csiro.au/am Australian Mammalogy species only, or all ranks), and the level of confidence in the taxon.…”
Section: Species Listsmentioning
confidence: 99%
“…taxID) and taxonomic names in the biodiversity domain, in a manner that is harmonised across repositories. This is exemplified by issues raised regarding the pressing need for collaborative efforts to build a common taxonomic framework ( Thiele et al 2021 ; Thomson et al 2021 ; Conix et al 2021 ; Lien et al 2021 ; Pyle et al 2021 ; Hobern et al 2021 ). This would provide tools to deal with synonyms and updates, it would enable better understanding of the meaning of a taxonomic name through access to taxonomic treatments, and it would facilitate annotations and links with external data.…”
Section: Introductionmentioning
confidence: 99%
“…They should also evolve, for instance, by taking into account representation issues, ranging from gender, race to regional biases. The recent proposal to unify avian checklists worldwide (Conix et al 2021;Hobern et al 2021;Lien et al 2021;Pyle et al 2021;Thiele et al 2021;Thomson et al 2021) is a true testament of the importance of the work being carried out by taxonomy committees, which provide a "summary" of avian diversity that can be easily used by multiple sectors within and beyond academia, including the birding community, nature lovers, journalists, bloggers, stakeholders, and policy-makers. While the advantages of having a single and standardized avian checklist for the entire planet are manifold, implementing this vision will be fraught with difficulties ranging from deciding on a given species concept to be applied consistently throughout all avian lineages based in most cases on fragmentary evidence, to paying the needed attention to inequality issues.…”
mentioning
confidence: 99%